The heat shock transcription factor 1 as a potential new therapeutic target in multiple myeloma. (18th December 2012) - Heimberger, Tanja; Andrulis, Mindaugas; Riedel, Simone; Stühmer, Thorsten; Schraud, Heike; Beilhack, Andreas; Bumm, Thomas; Bogen, Bjarne; Einsele, Hermann; Bargou, Ralf C.; Chatterjee, Manik
Summary The heat shock transcription factor 1 (HSF1) has recently been reported to promote malignant transformation and growth. Here we provide experimental evidence for a role of HSF1 in the pathogenesis of multiple myeloma (MM). Immunohistochemical analyses revealed that HSF1 was overexpressed in half of the investigated MM samples, including virtually all cases with extramedullary manifestations or anaplastic morphology. HSF1 function was inhibited either by siRNA‐mediated knockdown or pharmacologically through treatment with triptolide. Both approaches caused depletion of HSF1, lowered the constitutively high expression of a multitude of protective HSPs (such as HSP90, HSP70, HSP40 and HSP27), induced apoptosis in human MM cells in vitro, and strongly reduced MM tumour growth in vivo. Furthermore, we observed that treatment‐induced upregulation of HSPs after proteasome or HSP90 inhibition was critically dependent on HSF1. Importantly, the apoptotic effects of the HSP90 inhibitor NVP‐AUY922 or the proteasome inhibitor bortezomib were strongly enhanced in combination with triptolide, suggesting a salvage role of HSF1‐dependent HSP induction in response to drug treatment. Collectively, our data indicate that inhibition of HSF1 affects multiple protective HSPs and might therefore represent a therapeutic strategy – in particular in combination with proteasome or HSP90 inhibitors.